PU’UN TAM - DAHUN, ADET, ASEN: LANGUAGE, CULTURE, AND IDENTITY OF KAYAN ELDERS, SARAWAK, MALAYSIAN BORNEO - WAN, ROSELIND (2020)
This thesis investigates perception on language, culture, and identity of Kayan in Long Panai, Sarawak, Malaysian Borneo, and how Kayan language and culture shape cultural identity of the Kayan. Relying on ethnographic approach and a theoretical perspective that conceives Kayan language as endangered, linguistic, and cultural experiences of twenty (20) elders, aged between 50 to 80 at the time of the study provided context for exploration.